Spectrophotometric Study of Kinetics and Mechanism of Oxidation of o-Ethoxyaniline by Periodate Ion - Kaushik, R.D.; Kumar, Dharmendra; Kumar, Ajay; Malik, Rajdeep (Asian Journal of Chemistry, 2010)
The reaction between o-ethoxyaniline and periodate in acetone-water medium has been found to follow second order behaviour, being first order in each reactant. The rate of reaction decreases with decrease in dielectric constant of the medium. The reaction speeds up in presence of neutral salt. Free radical scavengers do not affect the reaction rate. The stoichiometry has been found to be 1 mol of o-ethoxyaniline: 2 mol of periodate. Thermodynamic parameters evaluated are: Ea = 18.2 kcal mol-1, A = 1.54 × 1012 dm3 mol-1 s-1; ΔS# = - 4.9 cal mol-1, ΔG# = 19.2 kcal mol-1 and ΔH# = 17.6 kcal mol-1. The derived rate law is in agreement with the results of kinetic studies. The rate law (k2) versus pH profile passes through the maximum. Main reaction product was characterized as ethoxy-1,4-benzoquinone. Molecular mechanism involving an iondipole interaction has been proposed on the basis of the kinetic studies and the reaction product isolated, separated and characterized.